Male Breast Cancer Has Limited Effect on Survivor's Perceptions of Their Own Masculinity: A Record Review and Telephone Survey of Patients in Johannesburg, South Africa. (March 2017) - Rayne, Sarah; Schnippel, Kathryn; Thomson, John; Reid, Joanna; Benn, Carol
The purpose of the current study was to describe male breast cancer in Johannesburg, South Africa, and assess whether male breast cancer patients' perception of their own masculinity was affected by having a cancer commonly seen in women. A retrospective file review was carried out at two hospitals, one private and one government, of male breast cancer patients from 2007 to 2012 followed by a telephone survey of patients identified during review. Of approximately 3, 000 breast cancer patients seen in the 5 years reviewed, 23 cases of male breast cancer were identified. Most were diagnosed with invasive ductal carcinoma ( n = 19, 83%). Stage at presentation was from stages 0 to 3 (Stage 0 [ n = 2, 9%], Stage 1 [ n = 3, 13%], Stage 2 [ n = 12, 52%], Stage 3 [ n = 6, 26%]) and no patients were metastatic at presentation. The telephonic survey was completed by 18 patients (78%). Nearly all ( n = 17/18) shared their diagnosis with family and close friends. Two thirds of patients delayed presentation and government hospital patients were more likely to present later than private sector hospital patients. Although most male breast cancer patients sampled did not perceive the breast cancer diagnosis as affecting their masculinity, Black men and those treated in government hospitals were less likely to be aware of male breast cancer, and were more likely to have their perception of their own masculinity affected.